2012
DOI: 10.1103/physrevd.86.032006
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and transverse spin asymmetries for inclusive jet production at mid-rapidity in polarizedp+pcollisions ats=200GeV

Abstract: We report STAR measurements of the longitudinal double-spin asymmetry A LL , the transverse singlespin asymmetry A N , and the transverse double-spin asymmetries A AE and A TT for inclusive jet production at mid-rapidity in polarized p þ p collisions at a center-of-mass energy of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 78 publications
(82 reference statements)
5
38
0
Order By: Relevance
“…These cross sections, along with others at ffiffi ffi s p ¼ 200 GeV for jets [18] and direct photons [19], are well described by the theory within its uncertainties, based on the method of varying the choice of scales by a factor of 2. In our previous publication [20], we examined the impact of this theoretical scale uncertainty with respect to our A π 0 LL results, and found that it is important and should be considered in future global analyses.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…These cross sections, along with others at ffiffi ffi s p ¼ 200 GeV for jets [18] and direct photons [19], are well described by the theory within its uncertainties, based on the method of varying the choice of scales by a factor of 2. In our previous publication [20], we examined the impact of this theoretical scale uncertainty with respect to our A π 0 LL results, and found that it is important and should be considered in future global analyses.…”
Section: Introductionmentioning
confidence: 79%
“…(15), includes, in addition to DIS and SIDIS data, final 2005 RHIC data [16,23] and preliminary versions of the 2006 RHIC data presented in [18,20,22]. The results of that analysis, which yields a much more accurate determination of ΔgðxÞ, are compared with A π 0 LL in Fig.…”
Section: The πmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also considered midrapidity data measured by the STAR collaboration for pp → jet X processes [85], where one can access directly the TMD-PDFs. On the other hand these data do not improve the constraint on the GSF due to the P T region explored and their relatively large error values.…”
Section: Jhep09(2015)119mentioning
confidence: 99%